The oxidant-antioxidant imbalance was involved in the pathogenesis of chronic rhinosinusitis with nasal polyps - Zhou, Jing; Zhou, Jiao; Liu, Ruowu; Liu, Yafeng; Meng, Juan; Wen, Qiao; Luo, Yirui; Liu, Shixi; Li, Huabin; Ba, Luo; Du, Jintao (Frontiers in Immunology, 2024)
Background Although oxidative stress is involved in the pathophysiological process of chronic rhinosinusitis with nasal polyps (CRSwNP), the specific underlying mechanism is still unclear. Whether antioxidant therapy can treat CRSwNP needs further investigation. Methods Immunohistochemistry, immunofluorescence, western blotting and quantitative polymerase chain reaction (qPCR) analyses were performed to detect the distribution and expression of oxidants and antioxidants in nasal polyp tissues. qPCR revealed correlations between oxidase, antioxidant enzymes and inflammatory cytokine levels in CRSwNP patients. Human nasal epithelial cells (HNEpCs) and primary macrophages were cultured to track the cellular origin of oxidative stress in nasal polyps(NPs) and to determine whether crocin can reduce cellular inflammation by increasing the cellular antioxidant capacity. Results The expression of NOS2, NOX1, HO-1 and SOD2 was increased in nasal epithelial cells and macrophages derived from nasal polyp tissue. Oxidase levels were positively correlated with those of inflammatory cytokines (IL-5 and IL-6). Conversely, the levels of antioxidant enzymes were negatively correlated with those of IL-13 and IFN-γ. Crocin inhibited M1 and M2 macrophage polarization as well as the expression of NOS2 and NOX1 and improved the antioxidant capacity of M2 macrophages. Moreover, crocin enhanced the ability of antioxidants to reduce inflammation via the KEAP1/NRF2/HO-1 pathway in HNEpCs treated with SEB or LPS. Additionally, we observed the antioxidant and anti-inflammatory effects of crocin in nasal explants. Conclusion Oxidative stress plays an important role in the development of CRSwNP by promoting various types of inflammation. The oxidative stress of nasal polyps comes from epithelial cells and macrophages. Antioxidant therapy may be a promising strategy for treating CRSwNP.